Hubungan Lingkungan, Pengetahuan, dan Sikap IRT dengan Perilaku Pencegahan Demam Berdarah Dengue - Mikael R. E. Nabu; Afrona E. L. Takaeb; Helga J. N. Ndun (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in Indonesia, including in Kupang City. This study aims to examine the relationship between environmental conditions, knowledge, and attitudes of housewives (IRT) and dengue prevention behaviors in the working area of Oesapa Public Health Center, Kupang City. This research is a quantitative study using a cross-sectional design. A total of 66 housewives were selected through purposive sampling. Data collection was conducted using questionnaires and observation sheets. Data analysis involved univariate and bivariate tests using the chi-square method with a significance level of 0.05. The research results show that the environmental variable has a significant relationship with dengue fever prevention behavior, as indicated by a p-value of 0.000 < 0.05. The knowledge variable does not have a significant relationship with dengue fever prevention behavior, as indicated by a p-value of 0.227 > 0.05. The attitude variable has a significant relationship with dengue fever prevention behavior, as indicated by a p-value of 0.000 < 0.05. In conclusion, dengue fever prevention behavior is more influenced by environmental conditions and attitudes than by the level of knowledge. This study recommends the need for interventions focused on improving attitudes and environmental conditions through education and active community participation.